Development of NILs from heterogeneous inbred families for validating the rust resistance QTL in peanut (Arachis hypogaea L.). Issue 1 (6th December 2013) - Yeri, Sharanabasappa B.; Shirasawa, Kenta; Pandey, Manish K.; Gowda, M. V. C.; Sujay, Vanhi; Shriswathi, Manda; Nadaf, Hajisaheb L.; Motagi, Babu N.; Lingaraju, S.; Bhat, A. R. S.; Varshney, Rajeev K.; Krishnaraj, P. U.; et al.
Abstract Heterogeneous inbred families segregating for rust resistance were identified from the two crosses involving susceptible (TAG 24 and TG 26) and resistant (GPBD 4) varieties of peanut. Rust‐resistant (less than score 5) and rust‐susceptible (more than score 5) plants were identified in each HIF and evaluated under rust epiphytotic conditions. The set of plants belonging to the same HIF, but differing significantly in rust resistance, not in other morphological and productivity traits, was regarded as near‐isogenic lines (NILs). Largely, rust‐resistant NILs had GPBD 4‐type allele, and susceptible NILs carried either TAG 24 or TG 26‐type allele at the three SSR loci (IPAHM103, GM1536 and GM2301) linked to a major genomic region governing rust resistance. Comparison of the remaining genomic regions between the NILs originating from each of the HIFs using transposon markers indicated a considerably high similarity of 86.4% and 83.1% in TAG 24 × GPPBD 4 and TG 26 × GPBD 4, respectively. These NILs are useful for fine mapping and expression analysis of rust resistance.